Anti-bacterial performance of azithromycin nanoparticles as colloidal drug delivery system against different gram-negative and gram-positive bacteria - Morteza Azhdarzadeh; Farzaneh Lotfipour; Parvin Zakeri-Milani; Ghobad Mohammadi; Hadi Valizadeh (Tabriz University of Medical Sciences, 2012)
Purpose: Azithromycin (AZI) is a new macrolide antibiotic with a better activity against intracellular gram negative bacteria in comparison with Erythromycin. The purpose of this research was to prepare AZI nanoparticles (NPs) using PLGA polymer and to compare the effectiveness of prepared nanoparticles with untreated AZI solution. Methods: AZI NPs were prepared by Modified Quasi-Emulsion Solvent Diffusion method. The antibacterial activities of prepared NPs in comparison with AZI solution were assayed against indicator bacteria of Escherichia coli (PTCC 1330), Haemophilus influenzae (PTCC 1623) and Streptococcus pneumoniae (PTCC 1240) using agar well diffusion. Inhibition zone diameters (IZD) of nano-formulation were compared to the corresponding untreated AZI. Mean Inhibitory Concentration (MIC) values of AZI were also determined using serial dilution method in nutrient broth medium. Results: Mean IZD of nano-formulations for all indicator bacteria were significantly higher than that of untreated AZI (P<0.01). The enhanced antibacterial efficacy was more dominant in the gram positive species. The MIC values of NPs against the tested bacteria were reduced 8 times in comparison to those of untreated AZI. Conclusion: These results indicated an improved potency of AZI NPs which could be attributed to the modified surface characteristics as well as increased drug adsorption and uptake.